Chemical characteristics and light-absorbing property of water-soluble organic carbon in Beijing: Biomass burning contributions. (November 2015) - Yan, Caiqing; Zheng, Mei; Sullivan, Amy P.; Bosch, Carme; Desyaterik, Yury; Andersson, August; Li, Xiaoying; Guo, Xiaoshuang; Zhou, Tian; Gustafsson, Örjan; Collett, Jeffrey L.
Abstract: Emissions from biomass burning contribute significantly to water-soluble organic carbon (WSOC) and light-absorbing organic carbon (brown carbon). Ambient atmospheric samples were collected at an urban site in Beijing during winter and summer, along with source samples from residential crop straw burning. Carbonaceous aerosol species, including organic carbon (OC), elemental carbon (EC), WSOC and multiple saccharides as well as water-soluble potassium (K + ) in PM2.5 (fine particulate matter with size less than 2.5 μm) were measured. Chemical signatures of atmospheric aerosols in Beijing during winter and summer days with significant biomass burning influence were identified. Meanwhile, light absorption by WSOC was measured and quantitatively compared to EC at ground level. The results from this study indicated that levoglucosan exhibited consistently high concentrations (209 ± 145 ng m −3 ) in winter. Ratios of levoglucosan/mannosan (L/M) and levoglucosan/galacosan (L/G) indicated that residential biofuel use is an important source of biomass burning aerosol in winter in Beijing. Light absorption coefficient per unit ambient WSOC mass calculated at 365 nm is approximately 1.54 ± 0.16 m 2  g −1 in winter and 0.73 ± 0.15 m 2  g −1 in summer. Biomass burning derived WSOC accounted for 23 ± 7% and 16 ± 7% of total WSOC mass, and contributed to 17 ± 4% and 19 ± 5% of total WSOC light absorption in winter and summer, respectively. It is noteworthy that, up to 30% of total WSOC light absorption was attributed to biomass burning in significant biomass-burning-impacted summer day. Near-surface light absorption (over the range 300–400 nm) by WSOC was about ∼40% of that by EC in winter and ∼25% in summer. Highlights: High and relatively stable levoglucosan concentrations were found in Beijing in winter. Light absorption from biomass burning to WSOC was evaluated in Beijing. Light absorption (300–400 nm) by WSOC relative to EC was ∼40% (winter) and ∼25% (summer). Residential biomass burning is non-negligible source to fine PM in Beijing winter.